Investigation of the Behaviors of Users’ Who Shop from E-Commerce Sites - Selçuk Kıran; Berkay Alan; İlkim Ecem Emre (Acta Infologica)
With the development of information technologies, traditional trading methods have also changed and the concept of e-commerce has emerged as a result of this change. In the field of e-commerce, which has a growing market share, in Turkey, there are several e-commerce sites that offer products and services in different categories. Within the scope of this study, the relationships between the frequency of shopping from e-commerce sites and different factors were examined, and at the same time, it was aimed to reveal the changing preferences depending on gender. For these purposes, a questionnaire was applied to 1176 users of e-commerce sites. Survey findings were analyzed with correlation, t-test and chi-square tests. As a result, different factors affecting the frequency of use of e-commerce sites and usage habits that differ according to gender groups have been revealed.